The PPE domain of PPE17 is responsible for its surface localization and can be used to express heterologous proteins on the mycobacterial surface. - Valentina Donà; Marcello Ventura; Michela Sali; Alessandro Cascioferro; Roberta Provvedi; Giorgio Palù; Giovanni Delogu; Riccardo Manganelli (PLoS ONE, 2013)
PPE represent a peculiar family of mycobacterial proteins characterized by a 180 aminoacids conserved N-terminal domain. Several PPE genes are co-transcribed with a gene encoding for a protein belonging to another family of mycobacterial specific proteins named PE. Only one PE-PPE couple has been extensively characterized so far (PE25-PPE41) and it was shown that these two proteins form a heterodimer and that this interaction is essential for PPE41 stability and translocation through the mycobacterial cell wall. In this study we characterize the PE11-PPE17 couple. In contrast with what was found for PE25-PPE41, we show that PPE17 is not secreted but surface exposed. Moreover, we demonstrate that the presence of PE11 is not necessary for PPE17 stability or for its localization on the mycobacterial surface. Finally, we show that the PPE domain of PPE17 targets the mycobacterial cell wall and that this domain can be used as a fusion partner to expose heterologous proteins on the mycobacterial surface.